Implementation of the PNS e-Performance Program at the DPRD Secretariat of North Sulawesi Province - Yulius, Sendow Ridel; Langkai, Jeane E.; Dilapanga, Abdul Rahman (International Journal of Information Technology and Education, 2023)
This research aims to find out how the e-Performance program is implemented in the DPRD Secretariat of North Sulawesi Province and the factors inhibiting the implementation of e-Performance. The research method used in this research is descriptive-analytical research using a qualitative approach. Based on the results of research conducted by the author, the following conclusions can be drawn: (1) e-Performance was developed to make it easier for officials to input activities or work and create Daily Work Reports (LKH). In addition, this application is expected to be able to become a supporting instrument for leaders in making decisions regarding employees, units, and work units (2) The implementation process is going well starting from holding socialization to supporting facilities (3) In filling out e-performance, obstacles are still found such as slow networks and sometimes application errors. (4) Rewards are a form of appreciation for employee performance in the form of performance allowances, while punishment is in the form of a 25% reduction in performance allowances.